MORAL FORMATION AND ITS LIMITS: A CASE STUDY OF ISLAMIC EDUCATIONAL ETHICS IN A MADRASAH TSANAWIYAH, EAST JAVA - Anna Qomariana; Achmad Fanani (ELite Journal : International Journal of Education, Language and Literature, 2025)
Islamic educational ethics play a central role in shaping students’ moral, spiritual, and intellectual development. This study examines how Islamic ethical values are understood, practiced, and internalized within an Islamic school context in East Java, Indonesia. Employing a qualitative case study design, the research involved 18 participants consisting of five Islamic education teachers, twelve eighth-grade students, and one school principal at a Madrasah Tsanawiyah. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using thematic analysis to identify patterns related to ethical understanding, classroom implementation, and moral internalization. The findings reveal that teachers conceptualized Islamic educational ethics through values such as adab (proper conduct), ikhlas (sincerity), amanah (responsibility), and respect for knowledge, whereas students primarily interpreted ethics as compliance with school rules and behavioral expectations. The study also found that ethical values were consistently enacted through classroom routines, including prayers, Qur’anic recitation, respectful greetings, collaborative learning, and teacher modeling. However, students’ moral internalization remained limited, as ethical behaviors were often motivated by external regulation rather than personal moral conviction, and opportunities for reflective discussion of ethical dilemmas were rarely provided. The study highlights a gap between the institutional emphasis on Islamic ethical education and students’ deeper moral development, suggesting the need for more reflective and student-centered pedagogical approaches in Islamic schools.